Jornal O Cearense: anúncios de livros de instrução e educação (1846 a 1856) - Rodrigues, Jisaline Fagundes (2021)
This work aimed to identify and analyze book’s reports at O Cearense’s journal, from 1846 to 1856, considering the circulation of ideas about instruction and education and its representation to society. The study identified, through 986 advertisement issues published at the respective periodical edition, observing established time frame, so called featured “ADVERTS”, organized in a specific section in which was also detected a book’s offer, applying strategies of dissemination outreach centered on society’s awakening and the intentions to influence pedagogical choices by the government and educational’s authorities. Among 986 analyzed editions, 786 have different ads which refer to the logic of society and government’s respective period; in 204 ads, there are indications of books on different kinds of knowledge – some only disclosed, others expressly recommended- observing its theoretical and/or methodological conception and its potential for application to education from that period. This resource articulates different sources: 1) Highlighted journal O Cearense, available at National’s Library’s web site; 2) Province’s President’s reports; 3) laws that regulated the instruction, available in electronic media (official sites); e 4) bibliography produced about the theme, available at official databases. Theorical and methodological support applied to the writing reasoning has observed the contribution of Burke (2008), Carr (2002), Foucault (2012), Ginzburg(1989); Chartier (1994, 2014), Almeida (2007), Vilella (2011), among many other writers which conceptions were essential to understand not only the circulation of ideas, by the newspaper- literate’s culture device-, but also the representation of what they wanted to spread as knowledge to that society, supported on books, at that time, publicized and recommended to public instruction, contemplating State’s, Clergy’s and other leader’s desired ideas of education and instruction, linked to many institutions that made up social setting.